NLRP1 Inflammasomes: A Potential Target for the Treatment of Several Types of Brain Injury - Mi, Liang; Min, Xiaobin; Chai, Yan; Zhang, Jianning; Chen, Xin (Frontiers in Immunology, 2022)
NLR family pyrin domain-containing 1 (NLRP1) is a member of the NOD-like receptor (NLR) family. The NLRP1 inflammasome consists of the NLRP1 protein, adaptor protein apoptosis-associated speck-like protein containing a CARD domain (ASC), and effector molecule pro-caspase-1. When stimulated, the inflammasome initiates the cleavage of pro-caspase-1 and converts it into its active form, caspase-1, then caspase-1 facilitates the cleavage of pro-inflammatory cytokines interleukin-1β (IL-1β) and interleukin-18 (IL-18) into their active and secreted forms. In addition, caspase-1 also mediates the cleavage of gasdermin D (GSDMD) and leads to pyroptosis, an inflammatory form of cell death. Pathological events that cause damage to the brain and result in neuropathological conditions can generally be described as brain injury. Neuroinflammation, especially that derived from NLRP1, plays a considerable role in the pathophysiology of brain injury, such as early brain injury (EBI) of subarachnoid hemorrhage (SAH), ischemic brain injury during stroke, and traumatic brain injury (TBI). In this article, a thorough overview of NLRP1 is presented, including its structure, mechanism of activation, and role in neuroinflammation. We also present recent studies that view NLRP1 as a target for the treatment of EBI, ischemic brain injury, TBI, and other types of brain injury, thus highlighting the perspective on NLRP1 as an effective mediator of catastrophic brain injury.